Beispiel Nr: 04
$ \text{Gegeben: } \\ p_1: y=a_1x^{2}+b_1x+c_1 \qquad p_2: y=a_2x^{2}+b_2x+c_2\\ \text{Gesucht:Schnittpunkte zwischen 2 Parabeln} \\ \text{Parabel-Parabel}\\ \textbf{Gegeben:} \\ p_1: y= x^2-4x+1 \qquad p_2: y= x^2-2x-1 \\ \\ \textbf{Rechnung:} \\f\left(x\right)= x^2-4x+1\qquad g\left(x\right)= x^2-2x-1\\ \bullet \text{Schnittpunkte zwischen zwei Funktionen} \\ f\left(x\right)=g\left(x\right) \\ x^2-4x+1= x^2-2x-1 \\ x^2-4x+1-( x^2-2x-1)=0\\ \\ -2 x+2 =0 \qquad /-2 \\ -2 x= -2 \qquad /:\left(-2\right) \\ x=\displaystyle\frac{-2}{-2}\\ x=1 \\ \\ \\ \text{Schnittpunkt }1\\ f(1)=-2\\ S(1/-2)\\$